Technological Progress and Economic Inequalities: An Empirical Approach for Colombia (1974-2015) - Sanabria Gómez , Segundo Abrahán (Universidad Pedagógica y Tecnológica de Colombia, 2022)
As developing economies move towards modernization, they progressively incorporate new technologies into production processes. However, the incorporation of technological progress is not homogeneous among the different branches of economic activity; therefore, their productivity gains are unequally distributed. This article provides explanatory elements on the relationship between technological progress and structural heterogeneity. The question guiding the research is: how does structural heterogeneity induce asymmetries in the exploitation of technological progress? The statistical and econometric results show that the incorporation of technological progress in the Colombian manufacturing industry is uneven, since the knowledge-intensive branches of activity have different productive capacities from those of the low knowledge-intensive industry. These capacities follow patterns associated with a factorial intensity in favor of fixed capital, which offers better possibilities for incorporating new knowledge.